HUBUNGAN ANTARA SELF – EFFICACY DENGAN KECEMASAN BERBICARA MAHASISWA PADA MATA KULIAH SEMINAR BIOLOGI JURUSAN PENDIDIKAN BIOLOGI UIN ALAUDDIN MAKASSAR - Hasrida Astina; Misykat Malik Ibrahim; Muchlisah Muchlisah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This research is research that is korelasional which aims to find out the correlation between self effcacy and communication apprehension of Biology Education Student. The method of sampling using simple random sampling with a population of 136 scattered into four classes are homogeneous with 68 people as the sample in this research. The instruments used are self effcacy scale and scale anxiety talking compiled by researchers based on indicators of each variabel.Analysis of the research of the correlation analysing using pearson product moment. Upon analysis it was found that there isa negative relationship between self effcacy with anxiety speaks at seminar of biology courses with grades nilai r =- 0,456 ( = 0,01). This means that the higher self effcacy students then lower the level of anxiety of passionate speeches, neither the opposite